Visualization of the distribution of anatase and rutile TiO2 crystals in Au/TiO2 powder catalysts by STEM–EELS spectrum imaging. (23rd May 2014) - Akita, Tomoki; Kohyama, Masanori; Yurimoto, Hisayoshi
<x xml:space="preserve">Abstract</x> Gold nanoparticles deposited on TiO2 supports exhibit high catalytic activity for various chemical reactions such as low‐temperature CO oxidation. The catalytic performance is sensitive to the structure of the TiO2 supports, as reported in the epoxidation of propylene. TiO2 powder (P‐25), widely used as the support for metal catalysts, contains both anatase and rutile TiO2 phases. It is important to distinguish these two crystalline phases at the nanoscale in order to understand the effect of the support structure in Au/TiO2 catalysis. In this study, the two‐phase distribution is analyzed using scanning transmission microscopy–electron energy‐loss spectroscopy (STEM–EELS). The distribution is revealed through multilinear least‐squares fitting on the basis of the difference in the energy‐loss near‐edge structure. The results obtained indicate that Au particles are preferentially deposited on rutile TiO2 in the deposition/precipitation process. The STEM–EELS spectrum imaging method, with its high energy and spatial resolutions, can be employed to determine the distribution of crystal phases, components, and valence states. Copyright © 2014 John Wiley & Sons, Ltd.